1991
DOI: 10.1149/1.2085342
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical and Optical Investigation of Polypyrrole/Polyethyleneoxide Latex Particles

Abstract: Submicronic polypyrrole/polyethylene-oxide (PPy/PEO) latex particles have been produced using PEO as the steric stabilizer and either FeCl~ or K2S208 as the oxidizing agent for pyrrole. Scanning electron micrographs show that the two types of PPy/PEO latex particles are of approximately the same size. From electrochemical and optical characterization (UV-vis spectra) of these particles, it was found that these latex particles can be electrochemically oxidized and reduced in an electrolyte of acetonitrile with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…However, it is consistent with the conductivities (typically 10 -2 to 10 0 S cm -1 ) of various polypyrrole colloids reported by many research groups. [20][21][22][23][24][25][26][27][28][29][30] This lower conductivity is not believed to be due to any reduction in the intrinsic conductivity of the polypyrrole. On the contrary, the Cl/N ratio of 0.25 calculated from elemental microanalyses and the IR spectrum 36 of the colloid both indicate that the conducting polymer component of the particles is in its heavily-doped, highlyconductive state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is consistent with the conductivities (typically 10 -2 to 10 0 S cm -1 ) of various polypyrrole colloids reported by many research groups. [20][21][22][23][24][25][26][27][28][29][30] This lower conductivity is not believed to be due to any reduction in the intrinsic conductivity of the polypyrrole. On the contrary, the Cl/N ratio of 0.25 calculated from elemental microanalyses and the IR spectrum 36 of the colloid both indicate that the conducting polymer component of the particles is in its heavily-doped, highlyconductive state.…”
Section: Resultsmentioning
confidence: 99%
“…In 1986 Bjorklund and Liedberg reported the first synthesis of colloid polypyrrole particles using methylcellulose in aqueous media . Subsequently, various research groups have shown that a wide range of both commercial and tailor-made , water-soluble polymers can be used as steric stabilizers for polypyrrole. These dispersions generally exhibit good long-term colloid stability: in our own laboratory we have samples which are more than six years old and exhibit no signs of flocculation.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of PPy in its colloidal forms has been sought to improve its processibility. Therefore, many kinds of steric stabilizers including poly(vinyl pyrrolidone) (PVP) [5], poly(ethylene oxide) (PEO) [6], poly(styrene sulfonate)(PSS) [7], poly(vinyl methyl ether) (PVME) [8,9], ethylhydroxycellulose [10] and so on have already been used to prepare PPy dispersions. Copolymers like poly(N-isopropylacrylamide-co-acrylamide) is also a candidate for stabilizing PPy dispersion [11].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] In these studies, the PPy "core" is surrounded by an outer layer of an adsorbed, solvated water-soluble polymer which acts as a steric stabilizer. Suitable stabilizers include methyl cellulose, poly(N-vinyl pyrrolidone), poly(vinyl acetate), poly-(ethylene oxide), and poly(vinyl methyl ether).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the processibility of these materials, some studies have been reported on the synthesis of sterically stabilized dispersions of PPy particles with submicrometer sizes. [7][8][9][10] In these studies, the PPy "core" is surrounded by an outer layer of an adsorbed, solvated water-soluble polymer which acts as a steric stabilizer. Suitable stabilizers include methyl cellulose, poly(N-vinyl pyrrolidone), poly(vinyl acetate), poly-(ethylene oxide), and poly(vinyl methyl ether).…”
Section: Introductionmentioning
confidence: 99%